Development of an anti-CAR antibody response in SIV-infected rhesus macaques treated with CD4-MBL CAR/CXCR5 T cells - Davey, Brianna C.; Pampusch, Mary S.; Cartwright, Emily K.; Abdelaal, Hadia M.; Rakasz, Eva G.; Rendahl, Aaron; Berger, Edward A.; Skinner, Pamela J. (Frontiers in Immunology, 2022)
T cells expressing a simian immunodeficiency (SIV)-specific chimeric antigen receptor (CAR) and the follicular homing molecule, CXCR5, were infused into antiretroviral therapy (ART) suppressed, SIV-infected rhesus macaques to assess their ability to localize to the lymphoid follicle and control the virus upon ART interruption. While the cells showed evidence of functionality, they failed to persist in the animals beyond 28 days. In this study, we examined the serum of the CD4-MBL CAR/CXCR5-T cell treated animals to determine whether the animals had developed an anti-CAR antibody response after infusion. All of the treated animals developed antibodies in their serum that bound to CD4-MBL CAR/CXCR5 T cells and the majority were capable of inducing an ADCC response. The CAR expressed on T cells included domains 1 and 2 of CD4, the carbohydrate recognition domain (CRD) of mannose-binding lectin (MBL), and an extracellular domain of the costimulatory molecule, CD28. The T cells also expressed CXCR5. Alternative CARs were transduced into target cells and used in a serum-binding assay in order to identify binding sites for the anti-CAR antibodies. A CD4 antibody-blocking assay suggests that the dominant immunogenic components of this CAR are the CD4 domains and the CD28 domain with its linker. This study shows that an anti-drug antibody (ADA) response can occur even when using self-proteins, likely due to novel epitopes created by abridged self-proteins and/or the self-domain of the CAR connection to a small non-self linker. While in our study, there was no statistically significant correlation between the ADA response and the persistence of the CD4-MBL CAR/CXCR5-T cells in rhesus macaques, these findings suggest that the development of an ADA response could impact the long-term persistence of self-based CAR immunotherapies.